Environmental DNA metabarcoding of cow dung reveals taxonomic and functional diversity of invertebrate assemblages. Issue 13 (15th December 2020) - Sigsgaard, Eva Egelyng; Olsen, Kent; Hansen, Morten D. D.; Hansen, Oskar Liset Pryds; Høye, Toke Thomas; Svenning, Jens‐Christian; Thomsen, Philip Francis
Abstract: Insects and other terrestrial invertebrates are declining in species richness and abundance. This includes the invertebrates associated with herbivore dung, which have been negatively affected by grazing abandonment and the progressive loss of large herbivores since the Late Pleistocene. Importantly, traditional monitoring of these invertebrates is time‐consuming and requires considerable taxonomic expertise, which is becoming increasingly scarce. In this study, we investigated the potential of environmental DNA (eDNA) metabarcoding of cow dung samples for biomonitoring of dung‐associated invertebrates. From eight cowpats we recovered eDNA from 12 orders, 29 families, and at least 54 species of invertebrates (mostly insects), representing several functional groups. Furthermore, species compositions differed between the three sampled habitats of dry grassland, meadow, and forest. These differences were in accordance with the species' ecology; for instance, several species known to be associated with humid conditions or lower temperatures were found only in the forest habitat. We discuss potential caveats of the method, as well as directions for future study and perspectives for implementation in research and monitoring.